2011
DOI: 10.1007/s00134-011-2144-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of levosimendan and glibenclamide on circulatory and metabolic variables in a canine model of acute hypoxia

Abstract: PurposeTo study the effects of pretreatment with levosimendan (LEVO, a Ca2+-sensitizer and KATP+ channel opener) and/or the KATP+ channel antagonist glibenclamide (GLIB) on systemic hemodynamics, metabolism, and regional gastromucosal oxygenation during hypoxic hypoxemia.MethodsChronically instrumented, healthy dogs (24–32 kg, n = 6 per group, randomized cross-over design) were repeatedly sedated, mechanically ventilated (FiO2 ~0.3) and subjected to the following interventions: no pretreatment, LEVO pretreatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 45 publications
0
19
0
1
Order By: Relevance
“…The dimension (e.g., diameter 2 mm) and flexibility of this miniaturized probes allow an endoscopic application, and have been applied by us in animal studies [56, 57], as well as in volunteers [58] and patients [59, 60]. …”
Section: Monitoring Of Tissue Oxygenationmentioning
confidence: 99%
“…The dimension (e.g., diameter 2 mm) and flexibility of this miniaturized probes allow an endoscopic application, and have been applied by us in animal studies [56, 57], as well as in volunteers [58] and patients [59, 60]. …”
Section: Monitoring Of Tissue Oxygenationmentioning
confidence: 99%
“…Schwarte et al [114] examined the effect of levosimendan on cardiac output and tissue perfusion in the presence of hypoxia in a canine model. They found that when levosimendan was infused before hypoxia was induced, myocardial contractility, stroke volume and cardiac output were preserved in spite of the hypoxic insult.…”
Section: Experimentalsmentioning
confidence: 99%
“…Cardiac output was determined via transpulmonary thermodilution (PiCCO 4.2 non US, PULSION Medical Systems, Munich, Germany) at the end of each intervention, for at least 30 min, as previously described [19,20]. Arterial oxygen content, systemic oxygen delivery (dO 2 ) and systemic vascular resistance (SVR) were calculated subsequently.…”
Section: Methodsmentioning
confidence: 99%